VARIABILITY STUDIES IN SORGHUM ( ARIABILITY STUDIES IN SORGHUM (Sorghum bicolor Sorghum bicolor (L.) Moench) .) Moench) GERMPLASM LINES FOR SHOOT FLY RESISTANCE PARAMETERS ARAMETERS. - H. V. KALPANDE, P. P. AMBILWADE, A. J. SYED*, A. W. MORE (The Bioscan, 2018)
Sorghum shoot fly (Atherigona soccata Rond.) one of the major constraints in sorghum production and host plant resistant is one of the components to control to sorghum shoot fly. The present study was carried out to assess the variability in sorghum germplasm lines for shoot fly resistant traits. The experiment was conducted in Randomized block design (RBD) with two replication on the farm of Sorghum research station, VNMKV, Parbhani during rabi 2015 with 116 sorghum germplasm lines and four checks one resistant check (IS-18551), one susceptible check (DJ-6514) and two varietal checks (SPV-1411 and PVK-801). Observations were recorded on the characters viz., deadheart percentage, trichome density, leaf glossiness, seedling vigour, leaf wetness, Plumule and leaf sheath pigmentation, chlorophyll content, plant height, leaf length, leaf breadth, leaf angle, days to 50% flowering, days to maturity, 100 seed weight and grain yield per plant. The data were collected and analyzed for genotypic and phenotypic coefficient of variation (GCV and PCV), heritability and expected genetic advance. Analysis of variance showed the significant variability for all the traits studied and suggesting the presence of wide range of variation among the genotypes for all the characters. The genotypic coefficient of variation was lower than the phenotypic coefficient of variation for all the characters, indicating their importance in hybridization programme for generating variability.